Uncontrolled manifold analysis of joint angle variability during table tennis forehand - Iino, Y.; Yoshioka, S.; Fukashiro, S. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to evaluate the variance structure of the trunk and racket arm joint angles in the table tennis topspin forehand in relation to the control of racket orientation using the uncontrolled manifold (UCM) approach. Seventeen (9 advanced and 8 intermediate) male collegiate table tennis players performed the strokes against backspin. The UCM analysis was conducted using 30 trial data per each participant. The degree of redundancy exploitation to stabilize the racket vertical and horizontal angles were not significantly different between the two performance levels, suggesting that the ability to exploit joint configuration redundancy may not contribute to achieving higher performance in sport hitting skill. The degree of redundancy exploitation is highest at ball impact and this result may reflect that the table tennis forehand is a fast interceptive task.